2020
DOI: 10.3390/ijerph17176239
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Consumer Behavior toward Foods Offered in Staff Canteens

Abstract: The aim of our study was to analyze the attitudes of employees toward food offered in staff canteens, to analyze their eating behavior and the factors determining the choice of meals in staff canteens. The survey was conducted on a sample of 600 adult respondents, who patronize staff canteens in Warsaw, Poland. The research enabled a detailed and comprehensive assessment of consumer behavior toward the use of staff canteens, as well as their opinions on the functioning of the canteens and meals offered. Factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…This contradicts the results found in a study carried out in a Brazilian university canteen, where menus influenced plate waste, pointing to the low variety of menus served as a contributor to food waste [34]. A study on the attitudes of employees toward food offered in staff canteens indicated a desire for variety, including vegetarian dishes, as well as health-promoting dishes [16]. The possibility of choosing between fish and meat and other options, as is the case of the workplace canteen where the study was conducted, allows higher satisfaction of consumer expectations and consequently lower waste values.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This contradicts the results found in a study carried out in a Brazilian university canteen, where menus influenced plate waste, pointing to the low variety of menus served as a contributor to food waste [34]. A study on the attitudes of employees toward food offered in staff canteens indicated a desire for variety, including vegetarian dishes, as well as health-promoting dishes [16]. The possibility of choosing between fish and meat and other options, as is the case of the workplace canteen where the study was conducted, allows higher satisfaction of consumer expectations and consequently lower waste values.…”
Section: Discussionmentioning
confidence: 63%
“…Food waste control in food service is a difficult task since it involves the consumers and their relationship with meals, both factors that may vary on a daily basis [10,[16][17][18]. Both service-related aspects, service quality and personal factors, are relevant to explain food waste [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, this consumer preoccupation with health in general, having transcended the “healthy lifestyle” trend [ 31 ], has now grown to become the main motivator for buyers or as the most highly valued attribute in the purchase of foods for consumption at home [ 32 , 33 , 34 , 35 ] and also when eating out [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by Czarniecka-Skubina et al [ 6 ] underlined the importance of workplace nutrition as a potential key intervention to reduce the incidence of chronic diseases in adult populations and improve public health via direct and indirect measures. The authors noted the importance of taking breaks, which plays a role in emotional exhaustion, job satisfaction, and organizational behavior.…”
mentioning
confidence: 99%